Economic Impact on Financial Ratios of Food Industry at Istanbul Stock Exchange Listed Firms - Atmaca, Metin; Demirel, Engin (International Journal of Economics and Financial Issues, 2017)
In this study, 22 food and beverage sector companies traded on the Istanbul Stock Exchange were selected as scope for the period 2008-2015. This research aims to investigate the relation between firm’s financial ratios and selected macroeconomic indicators which are income, poverty, and Gini coefficient value. Time series of financial ratios are obtained from firm’s financial statements. We show that as an economic indicator poverty levels and minimum wage has a significant relation on firm’s financial ratios which are cash ratio, sales profitability ratio, and net working capital ratio. This research found that only poverty level and minimum wage has a positive impact on cash and working capital financial ratios and negative impact on sales profitability ratios of listed firms. Keywords: Financial Ratio, Panel Data Models JEL Classifications: C23, L61, G30